Impact evaluation of energy interventions a review of the evidence. - Raitzer, David A
It reviews 85 impact evaluations of energy interventions in developing countries, summarizes findings on outcomes, identifies evidence gaps, and proposes ways forward. It notes that impact evaluation has so far focused on rural electrification and improved cookstoves, while most investments are in power generation and transmission. It highlights where future impact evaluation investments can best contribute new evidence and how such studies could be approached.